Poetry as a Pathway to Reading Success in the Primary Grades (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The purpose of this article is to integrate poetry into the kindergarten classroom in order to strengthen early reading skills, stimulate playful and meaningful interactions with language, and nurture deeper relationships among peers and within families. Bringing poetry into the primary grades is essential because these early years form the foundation for children’s attitudes toward reading and communication. Unfortunately, poetry is often not introduced until the middle grades, and when it is, the instruction tends to focus mainly on analyzing poems for cognitive skills such as identifying figurative language or understanding structure. By this stage, many students have missed the opportunity to experience poetry as something joyful, engaging, and emotionally expressive, making it harder for them to develop a genuine appreciation for it. This article will examine in greater depth why poetry is an ideal and versatile tool for teaching foundational reading skills, fostering creative language play, and building stronger, more meaningful relationships among children and between children and their families.